2011
DOI: 10.1152/ajpheart.00258.2011
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived NO, but not cyclic GMP, is required for hypoxic augmentation in isolated porcine coronary arteries

Abstract: Chan CK, Mak J, Gao Y, Man RY, Vanhoutte PM. Endotheliumderived NO, but not cyclic GMP, is required for hypoxic augmentation in isolated porcine coronary arteries. Am J Physiol Heart Circ Physiol 301: H2313-H2321, 2011. First published October 7, 2011 doi:10.1152/ajpheart.00258.2011.-The present study investigated the mechanism underlying the transient potentiation of vasoconstriction by hypoxia in isolated porcine coronary arteries. Isometric tension was measured in rings with or without endothelium. Hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 60 publications
7
63
0
Order By: Relevance
“…Subsequent findings demonstrated that such a phenomenon, termed hypoxic augmentation of vasoconstriction (5, 15), occurs in a number of blood vessel types (5,7,8,15,21,23,25,26) contracted with norepinephrine (7, 8), phenylephrine (23), PGF 2␣ (15,25), and the TP receptor agonist U-46619 (21), indicating that it is not unique for a specific vasoconstrictor. It occurs in isolated coronary arteries with but not without endothelium (5,15,25,26). The phenomenon is not affected by bosentan, a blocker of endothelin receptors (5), but is prevented by inhibitors of nitric oxide (NO) synthase (5,15,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent findings demonstrated that such a phenomenon, termed hypoxic augmentation of vasoconstriction (5, 15), occurs in a number of blood vessel types (5,7,8,15,21,23,25,26) contracted with norepinephrine (7, 8), phenylephrine (23), PGF 2␣ (15,25), and the TP receptor agonist U-46619 (21), indicating that it is not unique for a specific vasoconstrictor. It occurs in isolated coronary arteries with but not without endothelium (5,15,25,26). The phenomenon is not affected by bosentan, a blocker of endothelin receptors (5), but is prevented by inhibitors of nitric oxide (NO) synthase (5,15,25).…”
mentioning
confidence: 99%
“…It occurs in isolated coronary arteries with but not without endothelium (5,15,25,26). The phenomenon is not affected by bosentan, a blocker of endothelin receptors (5), but is prevented by inhibitors of nitric oxide (NO) synthase (5,15,25). Hypoxic augmentation also occurs in arteries without endothelium treated with an exogenous NO donor (5) and is prevented by inhibitors of soluble guanylyl cyclase (sGC), including methylene blue, 1H-[1,2,4]oxadiazolo [4,3,-a]quinoxalin-1-one (ODQ), and NS-2028 (5,15).…”
mentioning
confidence: 99%
“…One cannot win both ways. We have, over the years, been confronted with other counterintuitive effects of sGC inhibitors, in that they prevent endothelium-dependent hypoxic vasoconstriction (7)(8)(9). We believe (9-11) that this can be explained by "biased" enzymatic activity of sGC, leading to the production of the noncanonical (12) vasoconstrictor cyclic nucleotide, inosine 3′,5′-cyclic monophosphate.…”
Section: The Tail Sees the Lightmentioning
confidence: 99%
“…(1)] facilitate hypoxic vasoconstrictions (7), whereas PKG inhibitors do not affect them (8). Could it be that, like hypoxia, blue light by activating melanopsin initiates the production of noncanonical cyclic nucleotides by sGC?…”
Section: The Tail Sees the Lightmentioning
confidence: 99%
“…As shown by Gabor Rubanyi and Paul M. Vanhoutte [40], such contractions involve the transfer of an endothelium-derived mediator in the canine coronary artery. Paradoxically, the mediator in question appears to be nitric oxide, which activates soluble guanylyl cyclase [41]. The mechanism involved remained elusive until Yuasheng Gao reported at the symposium that hypoxia causes the latter enzyme to switch substrates and produce cyclic inosine monophosphate, which turns out to be a new second messenger causing coronary vaso constriction.…”
Section: Endothelium-dependent Hypoxic Contractionsmentioning
confidence: 99%